COVID-19 Pandemic in Dialysis Patients: The Swiss Experience - Rebecca Guidotti; Menno Pruijm; Patrice M. Ambühl (Frontiers in Public Health, 2022)
BackgroundChronic dialysis patients are classified as patients with increased risk for COVID-19. Knowledge about the incidence and survival of chronic dialysis patients infected with SARS-CoV-2 in Switzerland - a high-income country with high density of relatively small dialysis centers - is scarce. We present the findings regarding incidence, survival and regional differences, compared to those of the general population in Switzerland.MethodsInformation on chronic dialysis patients who tested positive for SARS-CoV-2 between February 24, 2020 and February 28, 2022 were reported to the Swiss dialysis registry by all 94 Swiss dialysis centers. Hereafter, these results were linked with clinical characteristics from the Swiss dialysis registry.ResultsThroughout the study period 1,120 out of ~4,700 dialysis patients tested positive for SARS-CoV-2 in Switzerland: 96 cases occurred in the first wave, 472 in the second wave and 5 in between. During the first wave, Italian-speaking Ticino was most severely affected, with a 7-fold higher incidence of dialysis patients compared to the general Swiss population. In the second wave, the majority of cases were found in the French-speaking part of Switzerland, with a 2.5 times higher incidence vs. non-dialysis patients. A total of 123 deaths were recorded in the first two waves, of which COVID-19 was the main cause of death in 100 patients. This corresponds to a highly increased overall mortality rate of 17.5% compared to 1.7% in the general population. Age was identified as the only risk factor for mortality in dialysis patients. During the third, fourth and fifth wave, 61, 43 and 443 cases, respectively, were recorded, resulting in 6 (mortality rate 9.8%), 1 (mortality rate 2.3%) and 13 deaths (mortality rate 2.9%).ConclusionChronic dialysis patients in Switzerland were more likely to be infected by SARS-CoV-2 during the first and second wave than the rest of the population, but an inverse trend was observed during the third, fourth and fifth wave, probably thanks to vaccination. In addition, mortality is significantly increased compared to non-dialysis patients. In Swiss dialysis patients, age is the strongest risk factor for death.